Learning Effectiveness of Guided Science to Improve Student Learning Outcomes - Anam, M. Chairul; Muzanni, Ahmad; Mujiburrahman, Mujiburrahman (Jurnal Ilmiah Sekolah Dasar, 2020)
The low learning outcomes of students in Natural Science is the main problem in this study. It is due to the ineffective science learning system in its application so that students are less interested in learning science. This study aimed to determine the effectiveness of using guided science discovery learning in improving learning outcomes of fifth grade elementary school students. The method used in this research is pre-experimental one group pretest-posttest design. The sampling technique used nonprobability sampling model, namely purposive sampling. The data analysis used was the effectiveness test using the paired sample t-test assisted by SPSS 21 through comparing the sig (2-tailed) value with an alpha value of 5%. The number of samples used was 28 students. The research instrument was a multiple-choice test and a questionnaire. The results showed that the mean pretest value was 59.29 and the posttest value was 0.082; the pretest significance was 0.126, the significance for the posttest was 0,082; the significance of guided science discovery learning was 0,200, each of which has a significance value of 0,000 <0, 05. It means that there is a significant difference, while the t value is 12,515. It means that the pretest score is smaller than the posttest, which is 12,515, so it can be stated that guided science discovery learning is effective in improving student learning outcomes. Thus, it can be concluded that there is a positive and significant effect of guided science discovery on learning outcomes of fifth grade elementary school students.